Efektifitas Penerapan Aroma Terapi Lemon Terhadap Pasien Pada Kehamilan Trimester Pertama Untuk Menurunkan Mual Dan Muntah Di Desa Mulyo Agung Sumatera Selatan - Leni Oktaviani; Dewi Kusumaningsih; Rilyani Rilyani (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2022)
ABSTRAK Mual pada ibu hamil dialami setiap pagi hari, tetapi ada pula yang terjadi setiap saat. Dari 50-90%Wanita hamil mengalami mual dan muntah selama trimester  pertama,  28%  mengalami mual  saja, sedangkan  52% mual yang disertai muntah. Gejalanya biasa muncul padaminggu ke-4 dan menghilang pada minggu  ke-16  danantara minggu ke-8 dan ke-12 akan mencapai puncak (Madjunkova et al.,2013). Setelah dilakukan implementasi, evaluasi yang di dapatkan pada klien dengan hasil. Diharapkan dapat menurunkan mual dan muntah yang dirasakan pada ibu hamil trimester pertama menggunakan penerapan aromaterapi lemon. Kata Kunci : Mual dan Muntah, Kehamilan Trimester I, Aromaterapi Lemon ABSTRACT Nausea in pregnant women is experienced every morning, but some occur at any time. From 50-90% of pregnant women experience nausea and vomiting during the first trimester, 28% experience nausea alone, while 52% experience nausea and vomiting. Symptoms usually appear in the 4th week and disappear at the 16th week and between the 8th and 12th weeks will reach a peak (Madjunkova et al., 2013). Mrs. R complains of nausea and vomiting in the morning and evening 6 times a day, especially after eating. Mrs. R said it was easy to feel tired after activities and decreased appetite, the client said that sometimes her head felt dizzy. In the second patient, Mrs. R At the initial complaint, the client came in with complaints of pregnancy in the first trimester, complaining of dizziness, nausea, feeling weak, decreased appetite, temperature: 37.5 0C, BP: 110/80 mmHg, conjunctiva slightly anemic. After implementation, the evaluation that is obtained on the client with the results of the problem is resolved. It is expected to recognize how the process of reducing nausea and vomiting felt in first-trimester pregnant women using the application of lemon aromatherapy. Keywords: Nausea and Vomiting, First Trimester Pregnancy, Lemon Aromatherapy